Analisis Kecenderungan Skripsi Mahasiswa Program Studi Pendidikan Agama Islam - M. Imamuddin (Edu Global : Jurnal Pendidikan Islam, 2022)
The purpose of this research is none other than to map the tendency of PAI student thesis who have completed their final assignment as a condition for obtaining a bachelor's degree. The research method used in this study is none other than library research. Researchers obtained data from the thesis documents of PAI students in the library. Thesis documents were randomly selected as 35 thesis documents which were students who had graduated in 2017-2019. Based on the documents obtained, then tabulation, analysis and conclusions are made. The results of the research show (1) the type of research that tends to be used is field research, (2) the method that tends to be used in research is descriptive quantitative, (3) research tends to be carried out in schools, namely in MTs equivalent, (4) research subjects tend to use students or students, and (5) the instruments that tend to be used are observation and interviews.